2018
DOI: 10.1051/0004-6361/201834082
|View full text |Cite
|
Sign up to set email alerts
|

New ultra-cool and brown dwarf candidates in Gaia DR2

Abstract: Context. The second Gaia data release (Gaia DR2) contains high-precision positions, parallaxes, and proper motions for 1.3 billion sources. The resulting Hertzsprung-Russel diagram reveals fine structures throughout the mass range. Aims. This paper aims to investigate the content of Gaia DR2 at the low-mass end and to characterize ultra-cool and brown dwarfs. Methods. We first retrieved the sample of spectroscopically confirmed ultra-cool and brown dwarfs in Gaia DR2. We used their locus in the precise Hertzsp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 45 publications
2
61
1
Order By: Relevance
“…2). There was only one object in common with the above mentioned subsample of 134 ob- jects from Smart et al (2019), and the missing VVV J17134060-39521521 was found among those 25 objects from Reylé (2018). These 25 UCD candidates are systematically brighter in absolute magnitudes (13.7 mag< M G <17.4 mag, with a peak at M G ≈15 mag) than the 134 objects from Smart et al (2019) (14.5 mag< M G <21.7 mag, with a peak at M G ≈17 mag).…”
Section: Known Ucds and Wdsmentioning
confidence: 86%
See 4 more Smart Citations
“…2). There was only one object in common with the above mentioned subsample of 134 ob- jects from Smart et al (2019), and the missing VVV J17134060-39521521 was found among those 25 objects from Reylé (2018). These 25 UCD candidates are systematically brighter in absolute magnitudes (13.7 mag< M G <17.4 mag, with a peak at M G ≈15 mag) than the 134 objects from Smart et al (2019) (14.5 mag< M G <21.7 mag, with a peak at M G ≈17 mag).…”
Section: Known Ucds and Wdsmentioning
confidence: 86%
“…The remaining two UCD candidate members of the Gaia DR2 20 pc sample from Smith et al (2018) are the L5 dwarf VVV J17264015-27380372 formerly discovered as VVV BD001 by Beamín et al (2013) and included in Smart et al (2019), and another mid-L dwarf candidate (with similar M G ≈16.7 mag and colour G−RP≈1.7 mag), VVV J17134060-39521521, that is missing in Smart et al (2019). Reylé (2018) searched for new UCD candidates in Gaia DR2 and found 14 915 objects, all with available G−RP colours, and provided spectral type estimates based on photometry. According to these estimates, given in the corresponding machinereadable table including only few of the original Gaia DR2 data (without errors), most of the candidates are late M dwarfs, whereas only 280 (<2%) are L dwarfs.…”
Section: Known Ucds and Wdsmentioning
confidence: 99%
See 3 more Smart Citations